Building a Robust A-P Axis - Heimberg, Alysha (Bentham Science Publishers, 2012)
Since the last common ancestor of Metazoa, animals have evolved complex body plans with specialized cells and spatial organization of tissues and organs. Arguably, one of the most significant innovations during animal evolutionary history was the establishment of a bilateral plane of symmetry on which morphological features (e.g. tissues, organs, appendages, skeleton) could be given specific coordinates within the animal along the anterior-posterior (A-P) and dorsal-ventral (D-V) axes. Hox genes are a known group of eumetazoan transcription factors central to regulating A-P patterning, but less well known and under current investigation is the broader regulatory landscape incorporating these genes, including microRNA (miRNA) regulation. The degree to which evolutionarily conserved targeting of Hox genes by Hox-embedded miRNAs contributes directly to A-P patterning is under investigation, yielding contrasting information dependent on the organism and miRNA of interest. The widespread A-P patterning defects observed in recent miR-196 loss-of-function studies solidifies the importance of miRNA regulation in Hox genetic hierarchies, and elucidating the developmental and evolutionary importance of all Hox-embedded miRNAs remains a challenge for the future.